2022
DOI: 10.1021/acscatal.2c00364
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation and Late-Stage C–H Functionalization by P450 TamI Are Mediated by Variant Heme-Iron Oxidizing Species

Abstract: P450-catalyzed hydroxylation reactions are well understood mechanistically including the identity of the active oxidizing species. However, the catalytically active heme-iron species in P450 iterative oxidation cascades that involve mechanistically divergent pathways and distinct carbon atoms within a common substrate remains unexplored. Recently, we reported the enzymatic synthesis of trifunctionalized tirandamycin O (9) and O′ (10) using a bacterial P450 TamI variant and developed mechanistic hypotheses to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Established catalysts for alkene epoxidation via high-valent metal-oxo complexes include Jacobsen’s manganese­(III)­salen complexes, synthetic metalloporphyrins, biomimetic non-heme iron complexes, and enzymes such as heme-dependent cytochrome P450 monooxygenases and peroxygenases or non-heme α-ketoglutarate-dependent dioxygenases . The exact mechanism of metal-oxo-mediated alkene epoxidation has long been controversial. ,,, A currently widely accepted view is that epoxide formation proceeds via an almost concerted reaction mechanism, potentially through an extremely short lived radical intermediate (Scheme ). Support for a concerted nature of the oxo transfer or a two-step mechanism in which the second step occurs very fast comes from the retention of the stereochemistry in epoxidation of cis -alkenes. ,,, It is believed that metal-oxo-mediated alkene to carbonyl oxidation proceeds from the radical intermediate via an electron/hydride transfer process including the formation of a carbocation species (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Established catalysts for alkene epoxidation via high-valent metal-oxo complexes include Jacobsen’s manganese­(III)­salen complexes, synthetic metalloporphyrins, biomimetic non-heme iron complexes, and enzymes such as heme-dependent cytochrome P450 monooxygenases and peroxygenases or non-heme α-ketoglutarate-dependent dioxygenases . The exact mechanism of metal-oxo-mediated alkene epoxidation has long been controversial. ,,, A currently widely accepted view is that epoxide formation proceeds via an almost concerted reaction mechanism, potentially through an extremely short lived radical intermediate (Scheme ). Support for a concerted nature of the oxo transfer or a two-step mechanism in which the second step occurs very fast comes from the retention of the stereochemistry in epoxidation of cis -alkenes. ,,, It is believed that metal-oxo-mediated alkene to carbonyl oxidation proceeds from the radical intermediate via an electron/hydride transfer process including the formation of a carbocation species (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…This study involves a new substrate for epoxidation catalyzed by P450 enzymes. P450 enzymes catalyze epoxidation reactions of chain terminal alkenes, [11,30] styrene, [31] and terpene derivatives, [32] and are used in the practical production of various high‐value compounds, such as tirandamycin [33] and mycinamicin [34] . Using NBE as a substrate, this study developed an efficient biological protocol for producing EPO‐NBE.…”
Section: Discussionmentioning
confidence: 99%
“…The Sherman group reported that TamI from Streptomyces sp. 307‐9 catalyzed the iterative oxidation of three positions of the bicyclic ketal moiety of tilanamycin C 44 , namely C10 hydroxylation, C11/C12 epoxidation, and C18 hydroxylation [70–73] . It is shown that TamI has good regio‐ and stereoselectivity for the oxidation of tilanomycin C 44 , and at the same time emphasizes the important role of multifunctional natural enzymes in catalyzing the synthesis of natural products.…”
Section: Cytochrome P450 Monooxygenases (P450s)mentioning
confidence: 99%